Strategy for Controlling the Electrical Conductivity of Indium Tin Oxide (ITO) Nanobranches - Lee, Dong Kyu; Choi, Kyoung Soon; Lee, Jaeyeong; Kim, Youngho; Oh, Sein; Shin, Hojun; Jeon, Cheolho; Yu, Hak Ki (Advanced Electronic Materials, 2019)
The electronic properties of indium tin oxide (ITO) nanobranches fabricated by electron beam evaporation are controlled using the following two methods: i) The growth direction of the rods and branches is controlled by an epitaxial relationship with a yttria-stabilized zirconia substrate. The aligned growth of ITO nanobranches causes low sheet resistance because of the high density and good connectivity of the branches. ii) Heterojunction metal-oxide nanoparticles are coated on the surface of the nanobranches to form a depletion region in the near surface for band bending. The morphology of the metal oxide also affects the electronic properties of the nanobranches. The sheet resistance of Fe2O3-coated nanobranches (Fe2O3: film shape) increases linearly with the number of coatings. In the case of Mn2O3 (Mn2O3: nanoparticle shape), the sheet resistance is dramatically increased and saturated with the increase in the number of coatings.
Keywords: Electrical conductivity; Electron beam evaporation; Epitaxial relationships; Growth directions; Indium tin oxide; Metal oxide nanoparticles; Nanoparticle shape; Yttria-stabilized zirconias (YSZ); heterojunction decoration; indium tin oxide (ITO) nanostructures; yttria-stabilized zirconia (YSZ) substrates